2008
DOI: 10.1136/bmj.39534.571042.be
|View full text |Cite
|
Sign up to set email alerts
|

Inequity of access to investigation and effect on clinical outcomes: prognostic study of coronary angiography for suspected stable angina pectoris

Abstract: Objectives To determine whether coronary angiography for suspected stable angina pectoris is underused in older patients, women, south Asian patients, and those from socioeconomically deprived areas, and, if it is, whether this is associated with higher coronary event rates. Design Multicentre cohort with five year follow-up. Setting Six ambulatory care clinics in England. Participants 1375 consecutive patients in whom coronary angiography was individually rated as appropriate with the Rand consensus method. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 30 publications
4
41
0
1
Order By: Relevance
“…106,107 In the United Kingdom, coronary angiography is underused in older people, women, south Asians, and people from deprived areas. 108 Appropriateness of CABG in northern New England in 2008 was 87.7%. 1 In 2006, 253,000 patients underwent CABG in the United States.…”
Section: Influenza Vaccinementioning
confidence: 99%
“…106,107 In the United Kingdom, coronary angiography is underused in older people, women, south Asians, and people from deprived areas. 108 Appropriateness of CABG in northern New England in 2008 was 87.7%. 1 In 2006, 253,000 patients underwent CABG in the United States.…”
Section: Influenza Vaccinementioning
confidence: 99%
“…To date, there are conflicting reports on the use of and outcomes associated with percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) among Asian patients with coronary artery disease. Sekhri et al (5) followed up on 263 South Asian and 1112 white patients deemed appropriate for angiography in England, and reported that South Asian patients were less likely to receive angiography than white patients within three years. Feder et al (6) examined 345 South Asian and 2167 white patients undergoing coronary angiography in one health trust in London, England (UK).…”
Section: Cardiac Procedures and Mortality Among Ethnic Patientsmentioning
confidence: 99%
“…Causes of death and admission to hospital were coded according to the International Classification of Diseases, 10th revision (ICD-10). Our primary outcome, used in all reports from this data set, 17,22 was death from coronary artery disease (ICD-10 codes I20-I25) as well as hospital admission because of an acute coronary syndrome (acute myocardial infarction, ICD-10 codes I21-I23) and unstable angina (ICD-10 codes I20.0-120.9, 124.0, I24.8, I24.9). The management outcomes were receipt of coronary angiography as a confirmatory diagnostic test and subsequent coronary revascularization (either percutaneous coronary intervention or coronary artery bypass surgery, whichever was first) within 3 years of a clinic visit.…”
Section: Outcomes and Follow-upmentioning
confidence: 99%
“…10,11 This has been attributed to vasospastic and microvascular angina in women 12 and to the higher prevalence of diabetes mellitus 13 and socio-economic deprivation 7 among South Asian people. Both women 14,15 and South Asian 16,17 patients are less likely than men and white people in general to undergo invasive management of angina. It has been proposed that differences in how these patients describe their symptoms may contribute to inequalities in medical care, 8,18 because the diagnostic validity of symptoms plays an important role in deciding appropriate clinical management.…”
mentioning
confidence: 99%